2023
DOI: 10.1101/2023.11.15.567231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De novo lipogenesis pathway is a vulnerability in IDH1 mutant glioma

Lubayna S Elahi,
Michael C Condro,
Riki Kawaguchi
et al.

Abstract: Histone deacetylases (HDACs) have a wide range of targets and can rewire both the chromatin and lipidome of cancer cells. In this study, we show that valproic acid (VPA), a brain penetrant anti-epileptic and histone deacetylase inhibitor, inhibits the growth of IDH1 mutant tumors in vivo and in vitro, with at least some selectivity over IDH1 wild type tumors. Surprisingly, genes upregulated by VPA showed no change in chromatin accessibility at the promoter, but there was a correlation between VPA downregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our study raises several intriguing questions for future exploration: (1) Is the identified axis of p53 inactivation -astrocyte infiltration -FA metabolism relevant also to primary brain tumors? Glioblastomas commonly inactivate p53 (86), and have been recently shown to depend on FAS (49,(87)(88)(89)(90), suggesting that our findings may be relevant to primary brain tumors as well. ( 2) What is the exact molecular mechanism by which p53 regulates FA metabolism in the context of BCBM?…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our study raises several intriguing questions for future exploration: (1) Is the identified axis of p53 inactivation -astrocyte infiltration -FA metabolism relevant also to primary brain tumors? Glioblastomas commonly inactivate p53 (86), and have been recently shown to depend on FAS (49,(87)(88)(89)(90), suggesting that our findings may be relevant to primary brain tumors as well. ( 2) What is the exact molecular mechanism by which p53 regulates FA metabolism in the context of BCBM?…”
Section: Discussionmentioning
confidence: 76%
“…Lipid availability has been shown to be restrictive for cancer cell growth in the brain ( 1315 , 4749 ). We therefore hypothesized that astrocytes might support BC cells by secreting key FAs, and that the uptake of these FAs might be p53-dependent.…”
Section: Resultsmentioning
confidence: 99%